The effects of introduction of the Sulawesi Endemic Stingless Bee Tetragonula cf. biroi from Sulawesi to Java on foraging behavior, natural enemies, and their productivity (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suhri AGMI, Soesilohadi RCH, Agus A, Kahono S. 2021. The effects of introduction of the Sulawesi Endemic Stingless Bee Tetragonula cf. biroi from Sulawesi to Java on foraging behavior, natural enemies, and their productivity. Biodiversitas 22: 5624-5632. The existence of species in an environment has gone through a long adaptation process to the natural environment. This study aims to determine the behavior of bees, pollen types, natural enemies, and products of the Sulawesi endemic bee Tetragonula cf. biroi in its natural habitat and after being introduced to Java. This research was conducted in North Luwu and Bone District, South Sulawesi, Indonesia, as the native habitat. Purworejo, Magelang, and Bantul District in Java as an introduction site. The observation of foraging behavior was recorded by scan sampling method; pollen identification using the acetolysis method. Natural enemies were observed directly and through interviews with beekeepers. The results showed significant differences in the number of T. cf. biroi that returned to the nest between native and introduced habitats (p value < 0.05). Pollen collected by T. cf. biroi in Sulawesi were more varied in type. The woody plants and tall trees dominate the types of pollen they collect in Sulawesi. The pollen collected in Java was dominated by ornamental plants, intentionally grown as feed. The attack of Small hive beetle and black soldier flies larvae caused the colony of T. cf. biroi to die and not produce honey optimally. Another problem is the T. cf. biroi nest is taken over by the local bee Tetragonula laeviceps.
Keywords: Competition, endemic bees, introduction, local bees, meliponiculture